Association of abdominal fat with metabolic syndrome components in overweight women: effect of menopausal status - Shigeharu Numao; Yasutomi Katayama; Yoshio Nakata; Tomoaki Matsuo; Masaki Nakagaichi; Kiyoji Tanaka (Journal of Physiological Anthropology, 2020)
Abstract Background The association between abdominal fat distribution and metabolic syndrome (MetSyn) components by menopausal status has yet to be explicated. The purpose of this study was to examine a cross-sectional association between abdominal fat compartments and MetSyn components in pre- and post-menopausal overweight Japanese women. Methods Of 212 overweight Japanese women, 76 pre-menopausal overweight (BMI ≥ 25) women (PreM age, 42.1 ± 5.9 years) and 87 post-menopausal overweight women (PostM: age, 56.2 ± 4.5 years) were analyzed in this study. Measurements were taken for body mass index (BMI), abdominal compartments [visceral fat (VF), subcutaneous fat (SF), superficial subcutaneous fat (SSF), and deep subcutaneous fat (DSF)], serum high-density lipoprotein cholesterol (HDLC), low-density lipoprotein cholesterol, triglycerides (TG), and fasting plasma glucose (FPG). Abdominal compartments were assessed using computed tomography. Results No significant differences were found for BMI, SF, SSF, or DSF between the PreM and PostM. Despite this, the PreM had a significantly smaller VF area than that of the PostM. However, the difference in VF area disappeared when age was adjusted for. VFA significantly correlated with HDLC, TG, and FPG independently of menopause status. Conclusions These results suggest that the effect of menopause status on the association between VF and MetSyn components is negligible. Abdominal subcutaneous fat compartments were not associated with MetSyn components in overweight women regardless of menopausal status.